NONLINEAR VIBRATIONS AND STABILITY OF VISCOELASTIC CYLINDRICAL SHELLS UNDER COMPRESSIVE LOADS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
In this article, the stability of a cylindrical shell is investigated in a geometric nonlinear setting. The cylindrical shell is subjected to static and dynamic influences. The shell material is orthotropic and has rheological properties that are described by the hereditary Boltzmann-Voltaire theory. The characteristic deflections equal to the shell thickness are taken as a criterion for dynamic buckling. As a result of the study, the character of measuring the deflection of the shell, taking into account the rheological properties of the material, was obtained. It was revealed that with an increase in the loading rate, the dynamic critical load increases several times in comparison with the static one.
Keywords: cylindrical; shell; static; dynamic; action; Boltzmann Voltaire's theory; viscosity; elasticity; ripple; nonlinearity; stability; geometry; deflection arrow; length; radius; number of halfwaves; generatrix